STUDENT PERCEPTIONS OF PRACTICAL TRAINING PROGRAMS’ CONTRIBUTION TO EMPLOYABILITY SKILLS IN MALAYSIA’S JOB MARKET - Farah Adilla Ab Rahman; Jeniwaty Mohd Jody; Noor Najwa Liyana Mohd Rafi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The gap between practical training programs and the employability skills required by Malaysia’s labour market remains a pressing challenge. Despite earning academic qualifications, many graduates struggle to meet employer expectations due to skill mismatches and limited hands-on experience. This study investigates final-year students’ perceptions of the efficacy of practical training programs in fostering employability skills at UiTM Seremban 3, Negeri Sembilan, Faculty of Administrative Science and Policy. Data were collected through standardised questionnaires and analysed using descriptive statistics and Pearson correlation. The results revealed strong positive correlations between practical training participation, perceptions of industrial training quality, and efforts to mitigate skills mismatches. Organised, skill-oriented training programs significantly enhanced students’ adaptability, collaboration, and problem-solving abilities. These findings underscore the need for proactive curriculum reforms and policy interventions to ensure graduates are equipped with skills aligned with evolving industry demands. The research aims to inform curriculum development and policy creation, enhancing graduate readiness for Malaysia’s competitive employment landscape.